The Effect of Different Beverages on Salivary pH in 12-Year-Old School Children in Chennai - Manipal, Sunayana; John, Joseph; Saravanan, S; Kumar, Pradeep (Journal of Orofacial Research, 2013)
Aim: This analytical study aims to evaluate the effect of different beverages on salivary pH in 12-year-old school children. Materials and methods: The course of different beverages on the salivary pH was evaluated among two groups. Group A subjects (n = 16) constituted children who had DMFT = 0 and group B subjects (n = 16) constituted children who had DMFT? 5. Five group of test beverages were chosen for the study (fresh fruit group, acidic group, milk group, drink fortified with calcium and phosphorous group and basal group). Baseline saliva and beverage parameters were evaluated. The pH change from 1 to 60 minutes was recorded and compared using t test. Results: It was shown in this study, that group B subjects had a more pronounced salivary pH fall than the group A subject and this was found to be statistically significant. Also the group B subjects’ salivary pH returned to the baseline values much later than the group A subjects. Conclusion: It could be concluded from this study that salivary pH fall is attenuated in the presence of dental caries posing a greater risk for quicker progression of dental caries.